O papel do Conselho de Curadores como órgão de controle interno da Universidade Federal do Ceará na percepção da administração superior da instituição - Távora, Renato Vasconcelos (2012)
The development of technologies in their various fields is founded in scientific research. It is what fosters the great innovations that reflect the improvement of people's lives. In Brazil, research is mainly carried out by universities with funding from the Federal Union and agreements with private organizations. However, these require large investments and must be monitored by internal and external control mechanisms. In the Federal Universities, the Court of Audit and the Audit Committee General's Office conduct the external control, subsidized by the internal control system of each institution. The Board of Trustees of the UFC - CONCUR is an advisory body of collective deliberation, a member of Senior Management of the Federal University of Ceará, which aims to perform the duties of monitoring economic and financial institution, following all its budget execution. Although it has been established for this function, the senior management of the UFC is currently in study to extend the work of the CONCUR to reach other sectors considered important. Thus, this paper aims to investigate the perception that the Senior Management of the UFC has about the new role of the Board of Trustees as an organ of internal control, after the establishment of Internal Audit, checking for overlap of work or conflicts of jurisdiction and to investigate changes are being planned for the CONCUR and how they are implemented in practice, focusing on integrated view of the acts of audit. The method research approach was exploratory and descriptive techniques of archival research and literature, direct observation and interviews. The population studied was limited to members of Senior Management directly or indirectly linked to the issue of internal control of the UFC. Changes in the action of the Board of Trustees, in fact, are being studied, including backed by substantial changes in the actual Rules of the Curator. However, proposing significant changes to the work of an organ as the Curator is no simple task. Thus, we see that there is still no definitive conclusions by the Senior Management on the new profile and new form of action of this important deliberative body higher.